APPLICATION OF STEAM TURBINES SIMULATION MODELS IN POWER GENERATION SYSTEMS - Bresolin, C. S.; Schneider, P. S.; Vielmo, H. A.; França, F. H. R. (Revista de Engenharia Térmica, 2006)
The goal of this work is to simulate partial load operation of steam turbines in different controlling modes. An isentropic efficiency function is associated to a specific steam turbine. The Schegliáiev and the Stodola’s Ellipse Law, relating levels of pressure with mass flow, are compared. The proposed operational modes are: a) sliding pressure; b) throttling valve; c) nozzle valve. As a conclusion, Schegliáiev and Stodola’s models leads to very similar results and the operational modes by valves establishes theoretical limits of operation for steam turbines. The sliding pressure control is more efficient considering design operation.